Mechanical harvesting of cell sheets: an efficient approach for bone and cartilage tissue engineering - Fatemeh Leisi Mehrabani; Yalda Alibeigian; Mohamadreza Baghaban Eslaminejad; Samaneh Hosseini (Stem Cell Research & Therapy)
Abstract Cell sheet engineering (CSE) has demonstrated significant promise for the advancement and application of tissue-engineered constructs in the fields of tissue engineering and regenerative medicine. In this technology, cells are cultured to form a monolayer, which is then detached from the culture surface as a complete sheet. This process preserves cell interactions, maintains cellular phenotypes and functions, and retains the integrity of the cell–extracellular matrix (ECM). A main characteristic of the cell sheet is its ability to retain the native ECM components secreted by cells. When the ECM is preserved in cell sheets, cells are surrounded by a much more biologically appropriate environment to increase their regenerative potential, thereby offering more native conditions for cell growth and differentiation. CSE has shown promising results in a wide range of applications, including bone and cartilage. The cell sheets can be directly transplanted to the target site, where they integrate with the host tissue and enhance regeneration. The main challenge in CSE is how to detach an intact cell sheet without disturbing the ECM and cell‒cell connections. There are various methods for removing cell sheets that lead to the harvesting of intact cell sheets. Among the various methods for harvesting cell sheets, temperature-responsive systems and mechanical peeling are the most common. Mechanical harvesting, in particular, is a simple, cost-effective, accessible method that is widely used in research, especially in the scope of bone and cartilage tissue engineering. This article aims to review the application of cell sheets in bone and cartilage tissue engineering, with a focus on practical and cost-effective mechanical harvesting methods.